A tanulás tanulását befolyásoló tényezők: Habók Anita: A tanulás tanulása. A tanulás hatékonyságát befolyásoló tényezők - Andrea; Szénási, Alíz (Iskolakultúra, 2021)
Several possible approaches exist to the topic of learning to learn. Anita Habók's book titled Learning to Learn - Factors Influencing Learning Effectiveness focuses on the theoretical background and the measurement of the topic. On the one hand she deals with the interpretation of the concept of learning to learn and the definition of measurement frameworks, and, on the other hand, she summarizes and draws conclusions from measurement results carried out with the participation of students and teachers.